Risk factors and prevalence of taeniasis among the Karen people of Tha Song Yang District, Tak Province, Thailand - Kusolsuk Teera; Chaisiri Kittipong; Poodeepiyasawad Akkarin; Sa-Nguankiat Surapol; Homsuwan Nirundorn; Yanagida Tetsuya; Okamoto Munehiro; Watthanakulpanich Dorn; Waikagul Jitra; Dekumyoy Paron; Komalamisra Chalit; Ito Akira (Parasite, 2021)
Taeniasis remains a prevalent public health problem in Thailand. National helminthiasis surveys report only the incidence of Taenia spp. eggs. The ability to differentiate Taenia species using morphological and molecular techniques is vital for epidemiological surveys. This study detected taeniasis carriers and other helminthic infections by Kato’s thick smear technique and identified the Taenia species by multiplex PCR. The study subjects were the ethnic Karen people in Tha Song Yang District, Tak Province, Thailand, bordering Myanmar. In total, 983 faecal samples from villagers were examined for helminthiases. Interview-based questionnaires were used to gather information on possible risk factors for infection. The prevalence of helminth infections was 42.7% (420/983), including single (37.3%, 367/983) and mixed infections (5.4%, 53/983). The most common infection (19.23%, 189/983) was Ascaris lumbricoides, whereas taeniasis carriers comprised 2.8% (28/983). Multiplex PCR of Cox1 was used for species identification of Taenia tapeworms, eggs, or both in 22 taeniasis carriers. Most of the parasites (20 cases) were Taenia solium, with two cases of Taenia saginata. Taenia saginata asiatica was not found in the villagers examined. The analysis of 314 completed questionnaires showed that a statistically significant (p < 0.05) risk of taeniasis was correlated with being male, a history of being allowed to forage during childhood, a history of seeing tapeworm proglottids, and a history of raw or undercooked pork consumption. Health education programmes must seek to reduce and prevent reinfection in these communities.